1998
DOI: 10.1021/cm970632t
|View full text |Cite
|
Sign up to set email alerts
|

Photoactivatable Cross-Linked Polyacrylamide for the Site-Selective Immobilization of Antigens and Antibodies

Abstract: This paper describes the synthesis, characterization, and photochemical behavior of a new light-activated material for the photoimmobilization of antigens. The material is a derivative of cross-linked polyacrylamide that incorporates photoactive o-nitrobenzyl carbamates. When irradiated, the polymer undergoes a photochemical rearrangement to produce primary amines that can be used as molecular attachment sites. We monitored the photoconversion of thin (1-2 µm) polymer films that were deposited on silicon wafer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 53 publications
0
25
0
Order By: Relevance
“…Several groups have recently explored the use of dynamic stimulus-responsive surface chemistries for cell patterning to overcome those obstacles. Approaches include thermo-active, 7,9 electrical-active, 8 and photo-active 10 chemistries. In general, all of these chemistries operate under the same principle: they can be switched from a state that prevents cell attachment to a state that promotes it.…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have recently explored the use of dynamic stimulus-responsive surface chemistries for cell patterning to overcome those obstacles. Approaches include thermo-active, 7,9 electrical-active, 8 and photo-active 10 chemistries. In general, all of these chemistries operate under the same principle: they can be switched from a state that prevents cell attachment to a state that promotes it.…”
Section: Introductionmentioning
confidence: 99%
“…A value of 56 pmol · cm −2 was found. Since there was no additional red shifted emission in the fluorescence spectrum (for spectrum, see Supporting Information) it was concluded that the density of the primary amines is rather low 43, 44. These data suggest a ratio between amino groups and carboxylic acid groups of 1:5.…”
Section: Resultsmentioning
confidence: 92%
“…Cross-linked polymer films are encountered in practice in various forms, such as protective organic coatings cross-linked in the course of film formation, stimuliresponsive materials for sensors and other devices, or electroactive layers. [21][22][23][24] Such films are excellent candidates for smart surfaces with sensing and actuating characteristics. The selection of the suitable Gibbs energy function is the first step.…”
Section: Swelling Of Adhering Filmsmentioning
confidence: 99%